INCREASING ELEMENTARY SCHOOL STUDENTS' INTEREST IN READING WITH THE WORDWALL METHOD: A SYSTEMATIC REVIEW - Yusri, Yusri; Salim , Herli; Nurulpaik, Lik (Universitas Muhammadiyah Makassar, 2025)
The reading interest of elementary school students in Indonesia is low, even though reading is the key to gaining knowledge and academic success. WordWall, an online interactive platform that allows teachers to create games and learning activities, promises to increase students' interest and motivation in the context of reading literacy. This study aims to evaluate the effectiveness of the WordWall method in increasing the reading interest of elementary school students. This study uses a systematic literature review approach using preferred reporting items for systematic reviews and meta-analyses (PRISMA) guideline. The subjects of the study were the 50 most relevant articles out of the 948 articles identified. Data collection techniques through systematic search and selection of articles. Data analysis is carried out by evaluating and synthesizing the results of the selected articles. The results show that WordWall consistently improves students' reading interest, motivation, and learning outcomes. Interactive features such as quizzes, puzzles, and pairing games make learning more enjoyable and encourage active student participation. Research also shows that WordWall is superior to conventional methods in creating a fun and interactive learning atmosphere. While WordWall is effective, its implementation still faces challenges such as the need for technology devices, content adaptation for various subjects, and teacher training. This research contributes by providing a comprehensive overview of the effectiveness of WordWall and highlighting the need for further research on long-term impact and implementation in a variety of school contexts.